Sensory innervation of the guinea pig colon and rectum compared using retrograde tracing and immunohistochemistry. Issue 9 (2nd April 2016) - Chen, B. N.; Olsson, C.; Sharrad, D. F.; Brookes, S. J. H.
Abstract: Background: Neurons in lumbar and sacral dorsal root ganglia (DRG) comprise extrinsic sensory pathways to the distal colon and rectum, but their relative contributions are unclear. In this study, sensory innervation of the rectum and distal colon in the guinea pig was directly compared using retrograde labeling combined with immunohistochemistry. Methods: The lipophilic tracer, DiI, was injected in either the rectum or distal colon of anesthetized guinea pigs, then DRG (T6 to S5) and nodose ganglia were harvested and labeled using antisera for calcitonin gene‐related peptide (CGRP) and transient receptor potential vanilloid 1(TRPV1). Key Results: More primary afferent cell bodies were labeled from the rectum than from the distal colon. Vagal sensory neurons, with cell bodies in the nodose ganglia comprised fewer than 0.5% of labeled sensory neurons. Spinal afferents to the distal colon were nearly all located in thoracolumbar DRG, in a skewed unimodal distribution (peak at L2); fewer than 1% were located in sacral ganglia. In contrast, spinal afferents retrogradely labeled from the rectum had a bimodal distribution, with one peak at L3 and another at S2. Fewer than half of all retrogradely labeled spinal afferent neurons were immunoreactive for CGRP or TRPV1 and these included the larger traced neurons, especially in thoracolumbar ganglia. Conclusions & Inferences: In the guinea pig, both the distal colon and the rectum receive a sensory innervation from thoracolumbar ganglia. Sacral afferents innervate the rectum but not the distal colon. Calcitonin gene‐related peptide immunoreactivity was detectable in fewer than half of afferent neurons in both pathways. Abstract : The extrinsic sensory innervation of the guinea pig rectum and colon were compared by retrograde tracing and immunohistochemistry. Both regions receive innervation from thoracolumbar spinal afferents; only the rectum was innervated by lumbosacral afferents and vagal afferents were very sparse to both regions. Fewer than half of all traced afferents contained either CGRP or TRPV1.